2015
DOI: 10.15663/ajte.v2i1.30
|View full text |Cite
|
Sign up to set email alerts
|

The effect of classroom activities on students’ interest and career aspirations towards technology

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…Boeve-De Pauw and colleagues (2020) also found that even a one-day intervention (visiting technology and science workshops) can have a positive impact on girls' interest in a STEM career. By focusing more on design and technology workshops and making them more accessible to girls by letting them develop their own design, opportunities can be created to make the hard sciences more attractive (Ardies et al, 2015b;Boeve-De Pauw et al, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Boeve-De Pauw and colleagues (2020) also found that even a one-day intervention (visiting technology and science workshops) can have a positive impact on girls' interest in a STEM career. By focusing more on design and technology workshops and making them more accessible to girls by letting them develop their own design, opportunities can be created to make the hard sciences more attractive (Ardies et al, 2015b;Boeve-De Pauw et al, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The challenge of the future lies not only in stimulating senior students for technological studies; interest in technology can be encouraged much earlier, already at the start of secondary education (Ardies, De Maeyer & Gijbels, 2015b).…”
Section: Young People and Stemmentioning
confidence: 99%
“…They make things and conduct experiments. Students often like this way of teaching and its participatory and interactive approach (Ardies et al, 2015b). Research shows that education is more powerful and effective in a relevant and authentic learning environment (Van Houte et al 2013).…”
Section: Technology Educationmentioning
confidence: 99%
See 2 more Smart Citations